Letter : German activity in the Basque Country - Lizaso, Jose I. de
012a-0082-001 Mr Tracey Autonomous Government of Euzkadi Basque Delegation. Spanish Embassy, 24, Belgrave Square S.W.1. 20th June 1938. The Editor, Labour, National Council of Labour, Transport House, Smith Square, S.W.1. Dear Sir, GERMAN ACTIVITY IN THE BASQUE COUNTRY It will be recalled that I recently issued on behalf of the Basque Government a statement which outlined German military, naval and air activities in the Basque country since the war finished there. This statement was denied by the Spanish rebels. The Basque Government then urged the rebels to invite representatives of the British and French High Command to visit the country and make their own investigations - to which suggestion no rebel response has been made. I now have pleasure in enclosing for your interest and comment a booklet containing excerpts from a Basque Government report, which gives very much more detail, not only of Germany's military intervention, but also her activities in Basque economic and political life. Should you find the map - showing details of the military activities - of interest, I hope you will make what use of it you think fit. J.I. de Lizaso DELEGATE OF THE BASQUE GOVERNMENT, LONDON. Encl : 292/946/12a/82